Alternative environment activities on both sides of the Atlantic: A Canada-Ireland consideration and comparison. (August 2021) - Robinson, Daniel B; Hall, Nathan; Costa, José da; Bradford, Brent
Due to the overemphasis of traditional sports at the expense of other movement domains in physical education (PE) programmes, there is a need to consider what factors might enable or limit PE teachers' incorporation of some of these other domains that can support student learning. The focus of this article is on one such marginalized domain – alternative environment activities (AEAs). AEAs can afford students a breadth of opportunities for moderate-to-vigorous physical activity in different environments (i.e. land, snow and ice, water, air) and improve environmental awareness and stewardship. This article reports on a comparative investigation of Nova Scotian (Canadian) and Irish PE teachers' incorporation of AEAs in their PE programmes. To understand what similarities or differences might exist with respect to these PE teachers' incorporation of AEAs, along with existing enablers and barriers, a self-selected sample of current PE teachers (Nova Scotia = 53; Ireland = 64) completed a 22-item online questionnaire. Descriptive and inferential statistical analyses were employed to conduct comparisons among the two data sets. PE teachers' understandings of curricular requirements for AEAs were found to be an issue in both Nova Scotia and Ireland. Reported significant differences include: AEA-related professional development participation; most important factors for deciding not to include AEAs; and feelings of school administrative support towards AEA incorporation. Findings also suggest that various issues may be hindering incorporation of AEAs in PE programmes, and that some of these issues do differ based on where the PE programme is situated.